Attitudes of Portuguese medical students towards euthanasia - Carrapatoso, Manuel Pedro; Nunes, Rui (Revista Bioética, 2021)
This study analyzes the opinions of medical students about euthanasia and physician-assisted suicide. Students from all Portuguese medical schools who attended the last year of the course and those who completed it in 2015/2016 were invited to the survey. To assess the association with religious beliefs, the Chi-square or the Fisher’s exact test was used. Of the 405 valid answers, most respondents were female, single, and with an average age of 24 years. Most reported religious beliefs and more than half had treated terminally ill patients. Regarding the legalization of euthanasia and assisted suicide, 73% and 56%, respectively, were in favor of these practices. Future Portuguese doctors are clearly in favor of euthanasia and physician-assisted suicide, unlike similar studies in other European countries.